Studying of vertigo in acute ischemic brain disorders in the vertebrobasilar system - Fedorchenko, Svitlana (ScienceRise: Medical Science, 2016)
The work is devoted to the study of vertigo in patients with acute ischemic brain disorders. The purpose of the study – studying the role of acute cerebral ischemia in the formation of vertigo in patients with focal and transient ischemic deficits in the vertebrobasilar system. Material and methods. The study is based on the results of a prospective analysis of 37 patients with acute cerebral pathology in vertebrobasilar territory. The patients were examined and treated in the neurological departments "Kharkiv State Clinical Hospital №7». We used clinical and neurological method, investigated the condition of the main arteries of the head, digital ultrasonic diagnostic scanning system. Brain structure was investigated on MRI. The study showed, that in acute manifestations of vascular disease in the vertebrobasilar system isolated vertigo is rare, most often a combination of vertigo occurs with neurological symptoms. Neuroimaging results did not conclusively interpreted the relationship of dizziness with acute cerebral ischemia in the vertebrobasilar system; further research with the assistance of modern technology in the form of magnetic resonance angiography of brain vessels, duplex ultrasonography, and statistical methods. The prevalence of high degree of stenosis (50% to 85%) of arteries of vertebrobasilar system at the ultrasound indicates a high risk of stroke in the population and the need to optimize the preventive measures. To solve the problems of early diagnosis and prevention of vertigo in acute ischemic cerebral disorders the program of preventive measures cerebrovascular disease should include screening ultrasound for the detection of this pathology already at an early (asymptomatic) stage of the disease